Platelet serotonin uptake and paroxetine binding among allelic genotypes of the serotonin transporter in alcoholics - Javors, Martin A. (2004)
Expression rates of long (L) and short (S) alleles of the serotonin (5-HT) transporter (5-HTT) gene have been shown to differ under various circumstances. We compared 5-HTT uptake (function) level and paroxetine binding (density) in platelets of alcoholics as indices of 5-HTT expression rate among LL, LS, and SS genotypes. Concentration curves of [(3)H]5-HT and [(3)H]paroxetine were used to quantify the equilibrium constant (Km) and maximum 5-HT uptake rate (Vmax) for 5-HTT uptake into intact platelets and the dissociation constant (Kd) and maximum specific binding density (Bmax) for paroxetine binding to platelet membranes, respectively. Genotypes were determined using electrophoresis with fluorescent markers. Vmax for 5-HTT uptake did not correlate with Bmax for paroxetine binding (r=−0.095, P=0.415). Means of Vmax and Bmax did not differ in a statistically significant manner among LL, LS, and SS genotypes in these alcoholic subjects. However, Vmax for LL and SS appeared to have a bimodal distribution, so the percentage of subjects with Vmax <200 fmol/min-10(7) platelets was statistically significantly higher in LL than in SS (51.5% vs. 22.7%, respectively), with an odds ratio of 3.6 (P<0.05). The percentage of Vmax <200 fmol/min-10(7) platelets for LS was 39.3% (not significant vs. LL or SS). Previous studies of healthy human controls have shown that 5-HTT density in raphe nuclei and 5-HTT uptake in platelets are higher in the LL genotype than in S carriers. Our findings in currently drinking alcoholics support the hypothesis that those with the LL genotype of the 5′-HTTLPR region of the 5-HTT gene have reduced 5-HTT function.